Care-Related Risk Factors for Hospital-Acquired Pressure Ulcers Among Elderly Hip Fracture Patients - Baumgarten, Mona (2012)
OBJECTIVES: To identify care-related factors associated with increased incidence of hospital-acquired pressure ulcers (HAPU) DESIGN: Prospective cohort study SETTING: Nine hospitals in Baltimore Hip Studies network PARTICIPANTS: 658 patients age ≥65 years who underwent surgery for hip fracture MEASUREMENTS: Skin examinations at baseline and alternating days until hospital discharge. Patients were deemed to have a HAPU if they developed ≥1 new pressure ulcers stage 2 or higher during the hospital stay. RESULTS: Longer emergency department stays were associated with lower HAPU incidence (>4-6 hours: adjusted incidence rate ratio [aIRR] 0.68, 95% confidence interval [CI] 0.48-0.96; >6 hours: aIRR 0.68, 95% CI 0.46-0.99, both compared to ≤4 hours). Patients with ≥24 hours between admission and surgery had a higher post-surgery HAPU rate than those with <24 hours (aIRR 1.62, 95% CI 1.24-2.11). Surgery with general anesthesia had a lower post-surgery HAPU rate than surgery with other types of anesthesia (aIRR 0.66, 95% CI 0.49-0.88). There was no significant association of HAPU incidence with timing or type of transport to hospital, or surgery duration. CONCLUSION: Most of the factors hypothesized to be associated with higher pressure ulcer incidence were either associated with lower incidence or were not significantly associated, suggesting that HAPU development may not be as sensitive to care-related factors as commonly believed. Rigorous studies of innovative preventive interventions are needed to inform policy and practice.